-6(1-5v)=54

-6(1 - 5v) = 54

Now multiply by -1 on both sides , we get

6(1 - 5v) = -54

Now multiply 6 in the bracket, we get

6 - 30v = -54

Now subtract 6 on both sides, we get

6 - 6 - 30v = - 54 - 6

- 30v = - 60

Now divide by - 30 on both sides, we get

- 30v / -30 = - 60 / -30

v = 2

Hence v = 2

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up